We can solve for
first by rewriting the system of first-order ODEs as a single second-order ODE in
:
Taking the derivative of the first ODE gives
![(\mathrm dx)/(\mathrm dt)=3x+2y+1\implies(\mathrm d^2x)/(\mathrm dt^2)=3(\mathrm dx)/(\mathrm dt)+2(\mathrm dy)/(\mathrm dt)](https://img.qammunity.org/2020/formulas/mathematics/college/midzm3nnd7wy402p7l0g9ur7n2my9wxvpq.png)
while solving for
gives
![(\mathrm dx)/(\mathrm dt)=3x+2y+1\implies2y=(\mathrm dx)/(\mathrm dt)-3x-1](https://img.qammunity.org/2020/formulas/mathematics/college/px7bmwfh1h3p8c5uyqovz6qkdhregt9dk8.png)
Then
![(\mathrm d^2x)/(\mathrm dt^2)=3(\mathrm dx)/(\mathrm dt)+2(-2x-y+1)](https://img.qammunity.org/2020/formulas/mathematics/college/qzlrvc9so7b7dgrv1l3fsbvsaluzayd4dl.png)
![(\mathrm d^2x)/(\mathrm dt^2)=3(\mathrm dx)/(\mathrm dt)-4x-2y+2](https://img.qammunity.org/2020/formulas/mathematics/college/kyqphgw3m551dh3rpnlhwprx07ovtewnxp.png)
![(\mathrm d^2x)/(\mathrm dt^2)=3(\mathrm dx)/(\mathrm dt)-4x-\left((\mathrm dx)/(\mathrm dt)-3x-1\right)+2](https://img.qammunity.org/2020/formulas/mathematics/college/w08v99cvl10bfkgs69f85pwlhwob4fucx8.png)
![\implies(\mathrm d^2x)/(\mathrm dt^2)-2(\mathrm dx)/(\mathrm dt)+x=3](https://img.qammunity.org/2020/formulas/mathematics/college/b8os5q91zhjuo35cx8vf861tsdoxbd5ael.png)
which is linear with constant coefficients, so it's trivial to solve; the corresponding homogeneous ODE
![x''-2x'+x=0](https://img.qammunity.org/2020/formulas/mathematics/college/l7vnok5hwbkrw2iiux3cqf3kbz0desj2v2.png)
has characteristic equation
![r^2-2r+1=(r-1)^2=0](https://img.qammunity.org/2020/formulas/mathematics/college/gc3lea4jmcijvsbyi0dronmnt7jw3f52ni.png)
with root
(multiplicity 2), so the characteristic solution is
![x_c=C_1e^t+C_2te^t](https://img.qammunity.org/2020/formulas/mathematics/college/qmasde8o9muq2oztafvqim9tfv7b4c9tk1.png)
For the non-homogeneous ODE, assume a particular solution of the form
![x_p=a\implies{x_p}'={x_p}''=0](https://img.qammunity.org/2020/formulas/mathematics/college/8tajweiznfviemzkq78lroq9i8s9bw5o1u.png)
Substituting these into the ODE gives
![0-2\cdot0+a=3\implies a=3](https://img.qammunity.org/2020/formulas/mathematics/college/6ptny1xsb9iflidl1ruxe1aytda6kis392.png)
Then the general solution for
is
![\boxed{x(t)=C_1e^t+C_2te^t+3}](https://img.qammunity.org/2020/formulas/mathematics/college/7jpejcrl9fmr1p4etwxa4o0wr1t1kg8fs2.png)
From here, we find
![(\mathrm dx)/(\mathrm dt)=C_1e^t+C_2(t+1)e^t](https://img.qammunity.org/2020/formulas/mathematics/college/q8vfxs06vjbtrwhfb9pnzp6c73ajwa04dt.png)
so that
![2y=(C_1e^t+C_2(t+1)e^t)-3(C_1e^t+C_2te^t+3)-1](https://img.qammunity.org/2020/formulas/mathematics/college/zotp900hzty9d17ohg3gj7s13rrhghzpz2.png)
![\implies\boxed{y(t)=\left(\frac{C_2}2-C_1\right)e^t-C_2te^t-5}](https://img.qammunity.org/2020/formulas/mathematics/college/w9uky14rotdmxyx3btgcky7zxytrgk041e.png)